PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS ANDROID MATERI BILANGAN BULAT SEKOLAH MENENGAH PERTAMA - Rohmah, Rosyidatur; Kurniawan, Choirul; Abidin, Munirul (Universitas Insan Budi Utomo, 2025)
This study aims to address the low learning motivation and difficulties faced by junior high school students regarding the topic of integers. This is a Research & Development study that aims to: (1) produce an immersive educational game medium based on the quiz.zep.us platform; (2) determine the media's validity (feasibility) level; and (3) determine the media's practicality level. The development model used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 16 seventh-grade students at MTS Miftahul Ulum Pujon. Data collection instruments included expert validation questionnaires and student response questionnaires. The data were analyzed using quantitative descriptive statistics. The results showed that: (1) The quiz.zep.us-based educational game product was successfully developed. (2) The media validity level obtained an average score of 88.75%, categorized as